102k views
4 votes
Which equation is equivalent to y = 2/3 – 6?

2 Answers

2 votes

Answer:

3y=2-12

Explanation:

we can multiply both sides by 3 to get

3y=2-12

User Ebbu Abraham
by
5.8k points
7 votes

Answer:

Another equation that is equivalent to y = 2/3 - 6 would be:

y = -16/3

Explanation:

If you were to divide 2 by 3, you'd get 0.6667. Subtracting 6 you would then get -5.333.

-16 ÷ 3 = -5.333.

Just to check if you answer is reasonable :)

Which of course means y could be -5.333

Not sure if this is the answer you are looking for but I hope this helps a bit!!

User Chen Hanhan
by
5.9k points